2001
DOI: 10.1007/bf03185126
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer correlations for air-water two-phase flow of different flow patterns in a horizontal pipe

Abstract: Heat transfer coefficients were measured and new correlations were developed for two-phase heat transfer in a horizontal pipe for different flow patterns. Flow patterns were observed in a transparent circular pipe (2.54 ern 1. D. and L/D=96) using an air/water mixture. Visual identification of the flow patterns was supplemented with photographic data, and the results were plotted on the flow regime map proposed by Taitel and Dukler and agreed quite well with each other. A two-phase heat transfer experimental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
2
7
0
Order By: Relevance
“…Matzain [14] compared the correlations recommended by Kim et al [13] with experimental data and found that the discrepancies between the predictions from correlations and experimental data are significant. Further investigation on heat transfer was suggested for twophase flow by Matzain [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Matzain [14] compared the correlations recommended by Kim et al [13] with experimental data and found that the discrepancies between the predictions from correlations and experimental data are significant. Further investigation on heat transfer was suggested for twophase flow by Matzain [14].…”
Section: Introductionmentioning
confidence: 98%
“…Based on experimental data collected from the open literature, Kim et al [13] evaluated 20 heat transfer correlations and made recommendations for different flow patterns. Matzain [14] compared the correlations recommended by Kim et al [13] with experimental data and found that the discrepancies between the predictions from correlations and experimental data are significant.…”
Section: Introductionmentioning
confidence: 99%
“…Both the void fraction and superficial velocity ratio are very large and exceed the applicability ranges of the all correlations (u a =u l,0 % 0.01 $ 100, for general two-phase flow) listed in the literature (Kim et al, 1999(Kim et al, , 2000. Figure 8 shows the experimental results of the inlet Nusselt number versus the air Reynolds number for b max ¼ 0.5.…”
mentioning
confidence: 94%
“…In general, previous studies concerning two-phase flow mainly investigated the various two-phase regime maps and heat transfer characteristics in large-scale tubes. Most recently, Kim et al (1999Kim et al ( , 2000 carried out the evaluations of several heat transfer correlations for two-phase flow with different flow patterns in vertical and horizontal large-scale tubes. They recommended some appropriate correlations for different flow patterns and tube orientations based on the tabulated and graphical results.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (1997) evaluated 20 heat-transfer correlations against experimental data collected from the open literature and made recommendations for different flow patterns and inclination angles. However, these recommended correlations did not give satisfactory predictions when compared with experimental results by Matzain (1999).…”
Section: Introductionmentioning
confidence: 99%